Effectiveness of infographic video-based health education in promoting diarrhea prevention behaviors among elementary school children - Reni Yulianti; Faiza Yuniati (Jurnal Cakrawala Promkes, 2026)
Diarrheal diseases remain a major cause of morbidity and mortality among children worldwide, particularly in developing countries such as Indonesia. Inadequate hygiene practices and limited health education contribute to the high incidence of diarrhea among school-aged children. Innovative and engaging educational approaches are needed to improve children’s preventive behaviors. This study aimed to assess the effectiveness of health education using video infographics in improving knowledge, attitudes, and practices (KAP) related to diarrhea prevention among elementary school children in Palembang, Indonesia. A pre-experimental study with a one-group pretest-posttest design was conducted among 104 students at Negeri 145 elementary school in Palembang. Participants received health education through video infographics covering proper handwashing, healthy eating habits, maintaining clean toilets, and appropriate waste disposal. Data on KAP related to diarrhea prevention were collected using structured questionnaires before and after the intervention. Data were analyzed to compare pretest and posttest scores. The intervention resulted in significant improvements across all measured outcomes. Mean knowledge scores increased from 6.07 to 14.13, attitudes from 28.16 to 61.36, and practices from 31.28 to 64.98 (p < 0.05 for all variables). These findings indicate that video-infographic-based education effectively enhanced children’s awareness and adoption of diarrhea-prevention behaviors. Health education using video infographics is an effective tool for improving knowledge, attitudes, and preventive practices related to diarrhea among elementary school children. However, sustaining healthy behaviors beyond the school environment remains challenging and requires continued support from parents and communities, as well as improvements in sanitation and environmental conditions.